Indigenization of hybrid rice development in Pakistan: Breeding prospects and approaches - Ahmed , Muhammad Shahzad; Siddique, Faiza; Satti, Abid Majeed; Ullah, Zabih; Hussain, Imtiaz (Journal of Pure and Applied Agriculture, 2023)
Rice is an exportable commodity in Pakistan, earning a foreign exchange of almost two billion dollars every year. The demand for rice has recently been increased due to surging wheat prices in the country and food security issues. To cope with these issues there is an opportunity to exploit heterosis in the form of hybrid development in rice. Hybrid rice is one of the emerging avenues in Pakistan. Pakistan is importing almost 500 tons of hybrid seed every year from China and other countries at a cost of huge foreign exchange. Punjab Agriculture Department claimed hybrid system development in Basmati rice and its testing is in process. There is a possibility of hybrid system development in coarse rice by using a three-line and two-line hybrid system. The two-line hybrid system is an emerging hybrid system nowadays in China, Philippines, India, and Bangladesh. There is a need to import novel genetic material from China, IRRI and other sources for the strengthening of indigenous hybrid rice breeding. In a two-line hybrid system Japonica type rice genotypes were mostly utilized as a source of male sterility and restorer lines are used that can produce seed under hot climatic conditions. Pakistan has favorable climatic zones for the two-line hybrid system of rice like